The effect of combined inhalation aromatherapy with lemon and peppermint on nausea and vomiting of pregnancy: A double-blind, randomized clinical trial - Farzaneh Safajou; Narges Soltani; Mohsen Taghizadeh; Zahra Amouzeshi; Maryam Sandrous (Wolters Kluwer Medknow Publications, 2020)
Background: Nausea and vomiting are almost inevitable features of pregnancy which have a serious impact on the quality of life of pregnant women. This study aimed to determine the effects of combined inhalation aromatherapy with lemon and peppermint on nausea and vomiting of pregnancy. Materials and Methods: The parallel randomized clinical trial was conducted on 90 pregnant women suffering from nausea and vomiting of pregnancy referred to health centers in Birjand-Iran- from February 2015 to August 2016. Participants were randomly divided into two groups. The combined lemon and peppermint essential oils were used as an inhaler for the intervention and the placebo for the control group. Both groups were trained to place three drops of the solution onto a cotton ball and keep it in a 3-cm distance of their nose. The intensity of nausea, vomiting and fatigue was assessed through 24-hour Pregnancy Unique Quantization of Emesis (PUQE-24) questionnaire and Fatigue Severity Scale (FSS), respectively. Results: Mean (SD) scores of nausea and vomiting intensity before the intervention and on the first day of intervention were not significantly different between the two groups, but became significant on the second, third, and fourth days of intervention. The results showed that the effect of time on the mean intensity of nausea and vomiting was significant in the aromatherapy group (F2,84 = 22.92, p < 0.001) but was not significant in the placebo group (F2,78 = 0.26, p = 0.836). Conclusions: The combined lemon and peppermint aromatherapy could reduce mild to moderate intensity of nausea and vomiting during pregnancy.